Phytochemical Screening And Antidiabetic Test Of Ethanol Extract Of Sapodilla Kecik Leaves (Manilkara kauki (L) Dubard) On Decreasing Blood Glucose Of Diabetic Rats - Purba, Novandi; Harahap, Urip; Hasibuan, Poppy Anjelisa Z. (Publisher Cv. Inara, 2023)
The development of traditional medicine needs to be carried out so that Indonesia's natural wealth can be utilized as effectively as possible to improve people's welfare. As with diabetes, some reputable traditional herbal medicines contain antidiabetic properties. Natural antidiabetic drugs derived from compounds isolated from plants can be used as an alternative to traditional medicine for diabetes because they have potential side effects. Diabetes can be treated alternatively by using various substances, especially those containing polyphenols, such as flavonoids. Sapodilla kecik (Manilkara kauki (L.) Dubard) from the Sapotaceae family is a type of plant used in traditional medicine; leaves, roots and bark can be used to treat diarrhoea in children, seeds can be used as a febrifuge, anthelmintic, and as an antileprotic. Secondary metabolites in sapodilla kecik leaves are flavonoids, alkaloids, tannins, triterpenoids and glycosides. This research was carried out by characterizing and screening phytochemicals to determine the content of compounds in Sapodilla kecik (Manilkara kauki (L.) Dubard) and carrying out antidiabetic tests on streptozotocin-nicotinamide-induced diabetic rats. The results showed that sapodilla kecik leaves fulfilled the simplicia characterization requirements. Sapodilla leaves contain secondary metabolites such as alkaloids, flavonoids, tannins, glycosides, saponins and steroids. The ethanol extract of sapodilla kecik leaves at a dose of 500 mg/Kg BW starting from the 4th day of treatment, a dose of 250 mg/Kg BW starting on the 8th day of treatment, and a dose of 125 mg/Kg BW starting on the 12th day was able to reduce the KGD of induced diabetic rats with nicotinamide and streptozotocin.